Investigation of the Electrochemical Reduction Process of the Molybdate Ions in the Tartaric Electrolytes - Vusala Asim Majidzade; Akif Shikhan Aliyev; Dunya Mahammad Babanly; Mahmood Elrouby; Dilgam Babir Tagiyev (Acta Chimica Slovenica, 2019)
The electrochemical reduction of molybdate ions in tartaric electrolyte has been investigated in this work. Kinetics and mechanism of the electrochemical process have been studied by cyclic and linear voltammetric polarization methods. The effect of the temperature, the rate of potential-scanning and the concentration of the molybdate ions on the electrochemical process has been also studied. By estimating the effective activation energy, it was revealed that the electroreduction process is accompanied by mixing kinetics control.